Subcellular localization of the antidepressant-sensitive norepinephrine transporter - Matthies, Heinrich JG (BioMed Central, 2009)
BACKGROUND: Reuptake of synaptic norepinephrine (NE) via the antidepressant-sensitive NE transporter (NET) supports efficient noradrenergic signaling and presynaptic NE homeostasis. Limited, and somewhat contradictory, information currently describes the axonal transport and localization of NET in neurons. RESULTS: We elucidate NET localization in brain and superior cervical ganglion (SCG) neurons, aided by a new NET monoclonal antibody, subcellular immunoisolation techniques and quantitative immunofluorescence approaches. We present evidence that axonal NET extensively colocalizes with syntaxin 1A, and to a limited degree with SCAMP2 and synaptophysin. Intracellular NET in SCG axons and boutons also quantitatively segregates from the vesicular monoamine transporter 2 (VMAT2), findings corroborated by organelle isolation studies. At the surface of SCG boutons, NET resides in both lipid raft and non-lipid raft subdomains and colocalizes with syntaxin 1A. CONCLUSION: Our findings support the hypothesis that SCG NET is segregated prior to transport from the cell body from proteins comprising large dense core vesicles. Once localized to presynaptic boutons, NET does not recycle via VMAT2-positive, small dense core vesicles. Finally, once NET reaches presynaptic plasma membranes, the transporter localizes to syntaxin 1A-rich plasma membrane domains, with a portion found in cholera toxin-demarcated lipid rafts. Our findings indicate that activity-dependent insertion of NET into the SCG plasma membrane derives from vesicles distinct from those that deliver NE. Moreover, NET is localized in presynaptic membranes in a manner that can take advantage of regulatory processes targeting lipid raft subdomains.